2020
DOI: 10.1002/cnma.202000042
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Intelligent Photosensitive Antibacterial Wound Dressing: Simultaneous Detection and Treatment of Bacterial Infection for Accelerated Wound Healing

Abstract: Antibacterial photodynamic therapy (APDT) is an encouraging therapy modality for bacterial infection. In this work, trithiophene aldehyde (3T‐CHO) as a new photosensitizers was isolated from Herba Ecliptae, and tryptophan (Trp) modified 3T‐CHO improve water solubility and reduced phototoxicity. The photosensitizer‐loaded vesicles were incorporated into a gel scaffold to obtain a wound dressing with detection and antibacterial function. Detection of the presence of pathogenic bacteria, such as Pseudomonas aerug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…(Right: P. aeruginosa with irradiated vesicles; Middle: P. aeruginosa with vesicles, in the dark; Left: P. aeruginosa ). Reproduced with permission [ 197 ]. Copyright 2020, WILEY.…”
Section: Antibacterial Smart Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Right: P. aeruginosa with irradiated vesicles; Middle: P. aeruginosa with vesicles, in the dark; Left: P. aeruginosa ). Reproduced with permission [ 197 ]. Copyright 2020, WILEY.…”
Section: Antibacterial Smart Hydrogelsmentioning
confidence: 99%
“…A further smart photosensitive antibacterial hydrogel was fabricated by Zhou et al. [ 197 ] They designed a hydrogel containing tryptophan-modified trithiophene aldehyde (3T-CHO) (3 ​TT) as a photosensitizer to create a dressing with detection and antimicrobial applications. Experiments showed that the released 3 ​TT (photosensitizer and antibacterial agent) was associated with toxins (pyocyanin released by P. aeruginosa or hemolysin released by S. aureus ).…”
Section: Antibacterial Smart Hydrogelsmentioning
confidence: 99%
“…In this case, the first external "back" stimulus means that an infection was detected (for example, through monitoring of physiological parameters), and only then the external trigger is activated. The time delay in the response can be important and Several works have also reported the combination of antimicrobial action (drug release) and simultaneous observation of bacteria-killing/survival [223,224]. Proposed approaches, based on optical changes and bacteria combating by nitric oxide or release of incorporated antimicrobial agents, which were not activated by an external stimulus, potentially provide back-response in the observation of bacteria-killing efficiency, which is an interesting opportunity for time-balanced application of coating triggering.…”
Section: Detect and Killmentioning
confidence: 99%
“…(I) Photographs of the wound healing model. Reproduced from Zhou et al., 2020 . Copyright 2020 Wiley-VCH Verlag GmbH and Co. KGaA, Weinheim.…”
Section: Intelligent Nanoparticle-based Dressings For Bacterial Wound...mentioning
confidence: 99%
“…In another work reported by Zhou et al, tryptophanmodified trithiophene aldehyde (3TT) as a new photosensitizer was loaded into vesicles and incorporated into a gel scaffold to obtain a wound dressing with detection and antibacterial functionalities. 93 The vesicles could be lysed by cytotoxins produced by pathogenic bacteria, thereby releasing the photosensitive antibacterial agent. This achieved a simultaneous intelligent detection and treatment of pathogenic bacteria (Figure 6G).…”
Section: Multiple-stimulimentioning
confidence: 99%